Bibliometric Analysis of Augmented Reality Research in Biology Learning in Secondary And Higher Education - Nabila Khaerunnisa; Febby Apriani; Ermafitriyana Ermafitriyana; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Applied Science and Technology, 2026)
This study aims to analyze the development of research on augmented reality in biology learning at secondary and higher education levels using a bibliometric approach. The data were obtained from relevant scientific publications and analyzed using VOSviewer to identify publication trends, topic mapping (co-occurrence), and author productivity. The results show that the number of publications increased and reached a peak before declining after 2020, indicating a shift from the exploration stage to more specific and in-depth development. The co-occurrence analysis reveals strong relationships among keywords such as teaching, knowledge, implementation, and ability, indicating that the research focuses not only on technology but also on learning processes and learning outcomes. Furthermore, the analysis of author productivity indicates that the research is still distributed and collaborative, with several dominant contributors but not concentrated within a single research group. Overall, the findings suggest that augmented reality has significant potential to improve the quality of biology learning, particularly in enhancing conceptual understanding, engagement, and students’ cognitive abilities.